The linguistic and communicative aspect of the professional communication of doctors - Rusalkina, L.; Grigoriev, E. (Journal of Education, Health and Sport, 2023)
Implementation of the process of speaking is impossible without communication, that is, the sequence of transmission and reception of information. Approximately half of the doctor’s working time is spent on meetings, telephone conversations, communication with patients and colleagues. The ability to speak is his professional duty. A doctor, who knows how to speak creates the impression of an expert in his field, inspires trust in patients, which is a guarantee of successful treatment results. A high level of development of professional communication skills will largely determine the effectiveness of a doctor’s work, his ability to logically and reasonably express his opinions, establish relationships with colleagues, and create a positive social and psychological microclimate in the team. At the same time, mistakes made in professional communication can hinder the effective performance of a doctor’s duties and negatively affect his career. The basis of conflicts that reduce the creative potential of medical personnel is a low level of communicative competence caused by the lack of knowledge about communication and the corresponding communicative skills. The main goal of this work is a comprehensive consideration of the linguistic and communicative aspect of the professional communication of doctors. The methods of work involve the study of the mentioned phenomenon of linguistic and communicative skills of doctors, systematization, and correction of the acquired knowledge.